Using analogies for introducing synchrotron light in high school - Vitor Acioly; Telecio Barbosa Neto; Antonio Carlos Fontes dos Santos (Universitas PGRI Kanjuruhan Malang, 2023)
The aim of this paper is to propose the use of analogies for teaching principles of synchrotron radiation for high-school students. Analogy is an important tool for teaching new abstract subjects based on familiar content. In this paper, we suggest the use of Teaching With Analogies Strategy (TWAS), which is an approach to overcome the didactic obstacles in introducing abstract physics content to students. The authors expect that this work mayÂ contribute to the students' understanding of synchrotron radiation, reflectingÂ the needs and interests of secondary school teachers.